Influence of the extracellular matrix on water mobility in subcortical gray matter. Issue 2 (14th September 2018) - Georgi, Jakob; Metere, Riccardo; Jäger, Carsten; Morawski, Markus; Möller, Harald E.
Abstract : Purpose: Water mobility in tissues is related to the microstructure that modulates diffusion and spin relaxation. Previous work has shown that the extracellular matrix (ECM) impacts water diffusion in cartilage. To investigate if similar contributions to image contrast exist for brain, which is characterized by a substantially lower ECM content, diffusion and relaxation were studied in fixed samples from goat and human thalamus before and after enzymatic digestion of ECM compounds. Selected experiments in human corpus callosum were included for comparing subcortical gray matter and white matter. Methods: Digestion of matrix components was achieved by treatment with hyaluronidase. Nonlocalized pulsed field gradient measurements were performed with b values between 0.6 and 18, 000 s/mm 2 at 3T and temperatures between 0°C and 20°C, in addition to T1 and T2 relaxation measurements. The data were fitted to multiexponential models to account for different water compartments. After the measurements, the samples were sliced and stained for ECM‐sensitive markers to verify efficient digestion. Results: Microstructural alterations associated with hyaluronan digestion did not lead to measurable effects on water diffusion or T 2 . However, T1 of the main relaxographic component, attributed to intra‐/extracellular water, decreased by 7%. Conclusion: Investigations with very strong gradients did not reveal a detectable effect on water diffusion or T 2 after hyaluronan removal, indicating that the brain ECM content is too low to produce a detectable effect. The subtle alteration of T1 upon hyaluronidase treatment might reflect a modulation of intercompartmental water exchange properties.